Preparation of β-cyclodextrin based adsorbents and their behaviour towards chromium(VI)-diphenylcarbazide complex removal from aqueous solution / Nurul Huda Mohd Yusof - Mohd Yusof, Nurul Huda (2011)
The adsorption of Cr(VI) ions from aqueous solution by β-cyclodextrin (β-CD) based polymer as an adsorbent was studied in a batch adsorptions experiments. Three types of adsorbent were synthesized, namely, β-CDCP-HMDI, β-CDCP-TDI and Si-TDI-βCD. The method was based on the complex reaction of Cr(VI) with 1,5-diphenylcarbazide (DPC) in acidic solution loaded on β-CDCP-HMDI and β-CDCP-TDI and Si-TDI-βCD. The adsorption isotherm and kinetics of the three adsorbent were studied. Equilibrium isotherm was analyzed according to classic Langmuir and Freundlich model. It shows that the Langmuir isotherm is better in describing the adsorption process for adsorbent β-CDCP-HMDI, while Freundlich isotherm is better for β-CDCP-TDI and Si-TDI-βCD. In order to analyze the kinetics data, two kinetic model, pseudo-first order and pseudo-second order were applied. It was found that the adsorption processes for all types of adsorbents followed second order kinetic. The thermodynamic parameters for the sorption have been evaluated. The thermodynamic study shows that the enthalpy (ΔH°) value is positive suggesting an endothermic nature of the adsorption and the negative value of free energy (ΔG °) indicated the spontaneous nature of adsorption.